Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/j.2161-0045.2014.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of Career Development Theory, Research, and Practice—2013

Abstract: This annual review of the career counseling and development literature presents a content analysis of refereed journal articles published in 2013. Four research questions guided the analysis: (a) What content topics were included in career development articles published in refereed journals in 2013? (b) To what extent are theory, research, and practice integrated in career development articles published in refereed journals in 2013? (c) What variation exists in the characteristics of career development article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 72 publications
2
48
0
1
Order By: Relevance
“…Established scholars have a hard time sifting through many studies to come to some conclusions about research in an area, and it may be hard for practitioners to take the time to do that sifting or make sense of the results they find. Sampson, et al (2014) also noted these as reasons for the researchpractice gap, adding that researchers and practitioners use different language, which cannot help solve the communication problem. Scientists do not talk enough to practitioners and vice versa.…”
Section: Integrating Research Into Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Established scholars have a hard time sifting through many studies to come to some conclusions about research in an area, and it may be hard for practitioners to take the time to do that sifting or make sense of the results they find. Sampson, et al (2014) also noted these as reasons for the researchpractice gap, adding that researchers and practitioners use different language, which cannot help solve the communication problem. Scientists do not talk enough to practitioners and vice versa.…”
Section: Integrating Research Into Practicementioning
confidence: 99%
“…In this chapter, I will discuss the importance of using theory in interventions, the importance of integrating research in theory development, and the importance of integrating theory, research, and practice together. As Sampson et al's, (2014) review of the 2013 career literature demonstrated, the field does not integrate these areas well. They found nearly half of the articles in 2013 focused only on research, a third on theory, and less than a quarter focused on practice.…”
mentioning
confidence: 99%
“…A conceptual framework for examining the integration of theory, research, and practice in vocational psychology was provided by Sampson et al (2014) as part of their review of articles appearing in the Career Development Quarterly.…”
Section: The Relevance Of Integrating Theory Research and Practicementioning
confidence: 99%
“…Although Sampson et al (2014) found that a number of articles based on constructivist theory were published in career development journals during 2013 (e.g., Savickas's life design theory), very few articles appearing in the JEC used constructivist theory. Yet, Sampson et al (2014) did identify that quantitative research methodologies were employed in 81.6% of the 2013 career articles they analyzed.…”
Section: The Challenges In Integrating Theory Research and Practicementioning
confidence: 99%
See 1 more Smart Citation